Relationship between macroeconomic variables and stock market indices: cointegration evidence from stock exchange of Singapore’s all-S sector indices - Ramin Cooper Maysami,; Lee, Chuin Howe; Mohamad Atkin Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2005)
The relationship between macroeconomic variables and stock market returns is, by now, well-documented in the literature. However, a void in the literature relates to examining the cointegration between macroeconomic variables and stock market’s sector indices rather than the composite index. Thus in this paper we examine the long-term equilibrium relationships between selected macroeconomic variables and the Singapore stock market index (STI), as well as with various Singapore Exchange Sector indices—the finance index, the property index, and the hotel index. The study concludes that the Singapore’s stock market and the property index form cointegrating relationship with changes in the short and long-term interest rates, industrial production, price levels, exchange rate and money supply. Implications of the study and suggestions for future research are provided